The impact of the Internet on the University of the Philippines Institute of Library and Information Science students a citation analysis - Peñaranda, Doven U.; Reside, Marie Desiree H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Students have a wide range of sources to choose from when doing researches. It is obvious that the Internet has had an effect on the research behavior of the Institute of Library and Information Science students conducting their theses and special problems. The researchers can retrieve information from the libraries, or on the Internet, or from both sources.
This study aims to determine the impact of Internet on the citation behavior of the students. This study determined the distribution of the source materials cited by students from the University of the Philippines Institute of Library and Information Science theses and special problems from 1998 up to 2003 using citation analysis. Cited e-sources from the said timeframe were verified for their availability in the Internet. A nonparametric test, Jonckheere-Terpstra (JT) Test, was used to test the increasing trend of the medians over the years. Chi-square test was used to formally test the difference in proportions of e-sources. A correlation analysis was performed to see if the behavior on certain kinds of sources is associated with another kind of source. There was a separate analysis for graduate and undergraduate theses and the same statistical tools will be employed on both.
Results of this study show that there is definitely an impact of the Internet on the University of the Philippines Institute of Library and Information Science students conducting their theses and special problems based on the results of the study. The impact of the Internet is the increasing trend of citing e-sources of the students, the Internet is becoming a significant information source of the students' researches, and the Internet citations are increasing for both undergraduate and graduate students from the year 1998 up to 2003.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Institute of Library and Information Science -- Dissertations, Academic; Internet research; Bibliographical citations